Makna Religiusitas bagi Kaum Waria - Prasetiya, Benny; Usman, M; Syamsi, M. Faisyal (Analisis: Jurnal Studi Keislaman, 2020)
Understanding in Islam generally says that Waria's behavior and orientation are cruel and condemned, but on the other hand they need the existence of religion in their lives, this fact makes religious transgenders experience psychological doubts and psychological conflicts between their choice to become transsexuals with internalization of religious teachings. that they get in religion. This research will discuss how the meaning of religiosity for transvestites? This type of research is descriptive qualitative using a phenomenological approach, from 6 (six) transvestites, researchers took 4 (four) transvestites, namely Yt, Mn, Li, and Nu. The taking of this object uses a purposive sample and also uses recommendations from key informants in the field. The results of this study indicate that Transvestites still believe in religion and all its teachings. For Waria that their current existence is not their will but the will of the Creator. This is proven by their carrying out all religious rituals. It's just that they still can not be a normal human being in general who likes other types. Although religion forbids the existence of waria, it is clear that they continue to respect religion and try not to pollute religion.